2023
DOI: 10.1162/netn_a_00324
|View full text |Cite
|
Sign up to set email alerts
|

Can hubs of the human connectome be identified consistently with diffusion MRI?

Abstract: Recent years have seen a surge in the use of diffusion MRI to map connectomes in humans, paralleled by a similar increase in processing and analysis choices. Yet these different steps and their effects are rarely compared systematically. Here, in a healthy young adult population (n = 294), we characterized the impact of a range of analysis pipelines on one widely studied property of the human connectome; its degree distribution. We evaluated the effects of 40 pipelines (comparing common choices of parcellation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 115 publications
1
6
1
Order By: Relevance
“…After demonstrating that instrength gradients direct traveling waves in a 2D network model, we explored if gradients exist in the human connectome and found that instrength increased from temporal and parietal towards frontal and occipital regions. In contrast to previous studies [65][66][67] , we quantified instrength patterns statistically with spectrospatial mode analysis and found similar gradients across different cohorts and parcellations. We only studied SCs with similarsized parcels, high spatial resolution (≥400 regions), and across many subjects (≥70 subjects) to ensure high quality estimates.…”
Section: Discussioncontrasting
confidence: 65%
“…After demonstrating that instrength gradients direct traveling waves in a 2D network model, we explored if gradients exist in the human connectome and found that instrength increased from temporal and parietal towards frontal and occipital regions. In contrast to previous studies [65][66][67] , we quantified instrength patterns statistically with spectrospatial mode analysis and found similar gradients across different cohorts and parcellations. We only studied SCs with similarsized parcels, high spatial resolution (≥400 regions), and across many subjects (≥70 subjects) to ensure high quality estimates.…”
Section: Discussioncontrasting
confidence: 65%
“…and the spatial location of high-strength hub nodes. We assess heavy-tailedness and identify hubs using the nonparametric procedure out-lined in [40, 56] (see Methods for more details). Briefly, this procedure entails identifying hubs as the right tail outliers of the strength distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Second, while the datasets covered a broad range of possible processing choices, they did not allow to delineate their individual effects on null model performance. As tools for multiverse analysis in connectomics are developed to facilitate the isolation of specific processing choices across a range of pipelines [40], future work can increasingly interrogate how they affect connectomes and downstream network analysis, including null network generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tractography exhibits well-documented biases whereby a) short-range connections are overrepresented, overshadowing longer-distance tracts; and b) larger brain regions appear disproportionately connected (i.e., connectivity is positively correlated with regional surface area). 59 To account for these issues, for both the test-retest and validation samples, we generated distance-based consensus structural connectivity matrices per the approach described in ref. 60 .…”
Section: Methodsmentioning
confidence: 99%